Safety Aspects of Sustainable Storage Dams and Earthquake Safety of Existing Dams - Martin Wieland (Engineering, 2016)
The basic element in any sustainable dam project is safety, which includes the following safety elements: ① structural safety, ② dam safety monitoring, ③ operational safety and maintenance, and ④ emergency planning. Long-term safety primarily includes the analysis of all hazards affecting the project; that is, hazards from the natural environment, hazards from the man-made environment, and project-specific and site-specific hazards. The special features of the seismic safety of dams are discussed. Large dams were the first structures to be systematically designed against earthquakes, starting in the 1930s. However, the seismic safety of older dams is unknown, as most were designed using seismic design criteria and methods of dynamic analysis that are considered obsolete today. Therefore, we need to reevaluate the seismic safety of existing dams based on current state-of-the-art practices and rehabilitate deficient dams. For large dams, a site-specific seismic hazard analysis is usually recommended. Today, large dams and the safety-relevant elements used for controlling the reservoir after a strong earthquake must be able to withstand the ground motions of a safety evaluation earthquake. The ground motion parameters can be determined either by a probabilistic or a deterministic seismic hazard analysis. During strong earthquakes, inelastic deformations may occur in a dam; therefore, the seismic analysis has to be carried out in the time domain. Furthermore, earthquakes create multiple seismic hazards for dams such as ground shaking, fault movements, mass movements, and others. The ground motions needed by the dam engineer are not real earthquake ground motions but models of the ground motion, which allow the safe design of dams. It must also be kept in mind that dam safety evaluations must be carried out several times during the long life of large storage dams. These features are discussed in this paper.